Production of lightweight geopolymer concrete with foam glass aggregate derived from cathode-ray glass waste - Sarah Kareem Mohammed Al-Saudi; Róbert Géber (Case Studies in Construction Materials, 2024)
This work focused on producing an eco-friendly lightweight structure by recycling the cathode ray tube glass waste (CRT-GW)to prepare a foam glass aggregate (FGA) and using metakaolin to prepare a geopolymer binder (GP). The geopolymer binder replaces cement to decrease the release of gas generated during cement production. The silicon carbide (SiC) was used as a foaming agent at 1 wt% to prepare the FGA. The foaming temperature effect was investigated for the FGA characterization included: bulk density, volume expansion, apparent porosity, uniaxial compressive strength, and leaching tests for lead and barium. The foam glass aggregate was sintered at different temperatures 725 °C, 750 °C, 775 °C, and 800 °C. These temperatures were selected depending on heating microscopy analysis results, where the maximum expansion height was 119 % at 800 °C. The main characterization ranges of foam glass were: bulk density 0.58–1.26 g/cm3, volume expansion 8–77 (vol%), uniaxial compressive strengths 1.55–9.98 MPa, and thermal conductivity 0.063–0.097 W/m.K.The lightweight geopolymer (LWGP) was prepared with 30 vol% of FGA sintered at different temperatures and 70 vol% of GP. These samples hardened at room temperature. The bulk density and compressive strength were measured for the lightweight geopolymer samples after a curing time of 28 days. A higher compressive strength was 9.11 MPa with a bulk density of 1.21 g/cm3 for lightweight geopolymer-containing foam glass aggregate sintered at 775 °C.